Moral Mediums: Spirit-Writing and the Cultural Construction of Chinese Spirit-Mediumship - Clart, Philip (Ethnologies, 2003)
AbstractPhilip Clart addresses spirit-mediumship as a contested cultural field in Chinese popular religion. Drawing on his own field research, primary texts such as morality books, and studies of spirit-mediumship across the Chinese cultural sphere, he demonstrates the existence of different and sometimes competing interpretations of mediumship. In particular, he describes the views held among Taiwanese spirit-writing cults (“phoenix halls”), where mediumship is governed by the rules of a moral universe. Since the gods are moral forces, so the medium possessed by them must be a person whose moral cultivation renders him or her akin to the gods. Morality becomes the precondition and basis of transcendence, and the union of deity and medium is thus seen as occurring between two entities that are essentially alike.